2016
DOI: 10.5194/esurf-4-175-2016
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive cycles of floodplain vegetation response to flooding and drying

Abstract: Abstract.Flooding is a key driver of floodplain vegetation productivity. Adaptive cycles provide a model for examining the productivity of semi-arid floodplain vegetation in response to hydrology. We examined the response of vegetation productivity (measured as NDVI) through a hypothesised adaptive cycle to determine whether the cycle repeats over time and how it is affected by differently sized flood events. The area of floodplain inundation was associated with an adaptive cycle that repeated in four flood ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The productivity response of vegetation within the Narran floodplain has previously been shown to have a distinct pattern consistent with an adaptive cycle (Thapa, Thoms, Parsons, ; Thapa, Thoms, Parsons, & Reid, ). The current study demonstrates that productivity responses for different vegetation community types are also consistent with an adaptive cycle.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The productivity response of vegetation within the Narran floodplain has previously been shown to have a distinct pattern consistent with an adaptive cycle (Thapa, Thoms, Parsons, ; Thapa, Thoms, Parsons, & Reid, ). The current study demonstrates that productivity responses for different vegetation community types are also consistent with an adaptive cycle.…”
Section: Discussionmentioning
confidence: 91%
“…Whether patterns in these responses can be considered as following distinct and repeated adaptive cycles and whether they can provide insight as to the sensitivity of floodplain plant communities to potential changes in state over the course of the adaptive cycle remain to be seen and are an obvious direction for future study (cf. Thapa, Thoms, Parsons, ; Thapa, Thoms, Parsons, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rooting depth influences metal mobilisation/immobilisation and element specific uptake into the roots which also affects the transfer into the shoots (Chrzan, 2016;Overesch et al, 2007). Thapa et al (2016) also demonstrated a change in semi-arid Australian floodplain vegetation productivity in response to flooding and drying cycles; flooding brings nutrients which increases net primary productivity. These changes in vegetation productivity could also initiate structural changes in floodplain vegetation communities in natural and semi-natural ecosystems (Overesch et al, 2007).…”
Section: Plantsmentioning
confidence: 97%
“…Heterogeneity is a feature of floodplain surfaces that influences diverse functional responses to flooding (Scown et al, 2016b). For example, floodplain inundation was shown by Thapa et al (2016;2020) to drive vegetation productivity responses through an adaptive cycle of wetting (r), wet (K), drying (Ω), and dry (α) phases. Adaptive cycles characterize a diversity of responses as a cycle comprised of four phases: exploitation (r), conservation (K), release (Ω), and renewal (α) (cf.…”
Section: Flow Chain Modelmentioning
confidence: 99%